A Non-Typical Course of the Disease and Some Problems of Care of a Patient with Multiple Sclerosis, after a Skin Transplant — A Case Report - Małgorzata Adamczyk (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Throughout the year in the department of internal diseases in Kolo there were treated several patients with multiple sclerosis. Their care was directed towards preventions from complications resulting from immobilization and treatment of already existing ones. Aim. The aim of this study was to describe some nursing problems with a patient suffering from multiple sclerosis after skin transplant and nursing interventions. Case Report. The study was conducted with the participation of a 39-year — old woman diagnosed with the disease in 2008. The case study was the method applied in this research. Research techniques included an open interview and the analysis of documents. As a research tool the worksheet for collecting data on the patient was used. Discussion. Total physical dependence of a person with MS is compensated by the support from the staff and the family. Anxiety is possible to overcome in the presence of family. Conclusions. The presence of the infection of multiple sclerosis causes a disease. Depression is an unfavorable factor for recovery. Appropriate nursing care and the use of special dressings contribute significantly to the process of decubitus wounds healing. The process of rehabilitation of the patient proceeds more smoothly in the presence of immediate family. (JNNN 2016;5(3):109–116)